Numerical analysis of river spanning rock U-weirs: evaluating effects of structure geometry on local hydraulics - Holmquist-Johnson, Christopher Lee, author; Watson, Chester C., advisor; Abt, Steven R., committee member; Thornton, Christopher I., committee member; Doe, William, committee member (Colorado State University. Libraries, 2011)
River spanning rock weirs are being constructed for water delivery as well as to enable fish passage at barriers and provide or improve the aquatic habitat for endangered fish species. Many design methods are based upon anecdotal information applicable to narrow ranges of channel conditions and rely heavily on field experience and engineering judgment. Without an accurate understanding of physical processes associated with river spanning rock weirs, designers cannot address the failure mechanisms of these structures. This research examined the applicability of a Computational Fluid Dynamics (CFD) model, U2RANS, to simulate the complex flow patterns associated with numerous U-weir configurations. 3D numerical model simulations were used to examine the effects of variations in U-weir geometry on local hydraulics (upstream water surface elevations and downstream velocity and bed shear stress). Variations in structure geometry included: arm angle, arm slope, drop height, and throat width. Various combinations of each of these parameters were modeled at five flow rates: 1/10 bankfull discharge, 1/5 bankfull discharge, 1/3 bankfull discharge, 2/3 bankfull discharge and bankfull discharge. Numerical modeling results duplicated both field observations and laboratory results by quantifying high shear stress magnification near field and lab scour areas and low shear stress magnification near field and lab depositional areas. The results clearly showed that by altering the structure geometry associated with U-weirs, local flow patterns such as upstream flow depth, downstream velocity, and bed shear stress distributions could be altered significantly. With the range of parameters tested, the maximum increase in channel velocity ranged from 1.24 to 4.04 times the reference velocity in the channel with no structure present. Similarly, the maximum increase in bed shear stress caused by altering structure geometry ranged from 1.57 to 7.59 times the critical bed shear stress in the channel for a given bed material size. For the range of structure parameters and channel characteristics modeled, stage-discharge relationships were also developed utilizing output from the numerical model simulations. These relationships are useful in the design process when estimating the backwater effect from a structure for irrigation diversion as well as determining the spacing between structures when multiple structures are used in series. Recommendations were also made, based on the analysis and conclusions gathered from the current study, for further research. The analysis and results of the current study as well as laboratory studies conducted by Colorado State University and field reconnaissance by the Bureau of Reclamation provide a process-based method for understanding how structure geometry affects flow characteristics, scour development, fish passage, water delivery, and overall structure stability. Results of the numerical modeling allow designers to utilize the methods and results of the analysis to determine the appropriate U-weir geometry for generating desirable flow parameters (i.e. upstream flow depth and downstream velocity and bed shear stress magnification) to meet project specific goals. The end product of this research provides tools and guidelines for more robust structure design or retrofits based upon predictable engineering and hydraulic performance criteria.
Keywords: river restoration; rock weirs